Optimization and modeling of the performance of polydimethylsiloxane for pervaporation of ethanol−water mixture - Zentou, Hamid; Zainal Abidin, Zurina; Yunus, Robiah; Awang Biak, Dayang Radiah; Issa, Mohammed Abdullah (John Wiley & Sons, 2020)
Response surface methodology was used to optimize the performance of pervaporation of ethanol aqueous solution using polydimethylsiloxane hollow-fiber membrane. The effects of four operating conditions, that is, the feed temperature (30–50°C), the feed flow rate (10–50 L/h), ethanol concentration (5–20 wt%), and the vacuum pressure (10–50 KPa) on the membrane selectivity and the total flux of permeation were investigated with response surface methodology. The results showed that a quadratic model was suggested for both selectivity and total flux showing a high accuracy with R2 = 0.9999 and 0.9995, respectively. The developed models indicated a significant effect of the four studied factors on both selectivity and total flux with some significant interactions between these factors. The optimum selectivity was 15.56, achieved for a feed temperature of 30°C, feed flow rate of 10 L/h, ethanol concentration of 15 wt%, and a permeate pressure of 10.74 KPa whereas the optimum total flux was 1833.66 g/m2.h was observed for at a feed temperature of 50°C, a feed flow rate of 50 L/h, ethanol concentration of 15 wt%, and a permeate pressure of 49.38 KPa.